An integrated remediation system using synthetic and natural zeolites for treatment of wastewater and contaminated sediments (2011)
The major sources of water pollution can be classified as municipal, industrial, and agricultural. Different types of polluted aqueous effluents and sediments may be produced, which contain relatively high levels of heavy metals. During the 1990s, the large-scale development of constructed wetlands around the world drew much attention from public and environmental groups.The present study looks at the use of an integrated remediation system using zeolites for the treatment of wastewater and sediments.Zeolites have been widely studied in the past 10 years due to their attractive properties such as molecular-sieving, high cation exchange capacities, and their affinity for heavy metals. Coal industry by- products-based zeolites (faujasite type) have been tested as an effective and low-cost novel alternative for wastewater treatment, particularly their removing of heavy metals. On the other hand, a preliminary laboratory-scale experiment was conducted on the use of natural zeolites (clinoptilolite type) for the retention of heavy metals from canal sediments. Experimental work revealed promising results, which could be replicated on a bigger scale.Although this has been developed for canal sediments, the remediation strategy can be adapted to different waterways such asrivers. The development of the proposed remediation system in a specific experimental site as the major part of an innovation parkcan provide great benefits to a population living near contaminated effluents. It provides not only opportunities for the mitigation of environmental impact, improving water quality and landscape amenity, but also allows for several recreational opportunities.